A case report of intracardiac bone cement embolization after posterior decompression and cement-enhanced pedicle screw fixation for osteoporosis and lumbar degeneration. Issue 8 (25th February 2022) - Sun, Kui; Huang, Fuli; Liang, Biru
Abstract: Rationale: Bone cement leakage is a common complication of percutaneous kyphoplasty (PKP) and percutaneous vertebroplasty (PVP) surgery and has also been reported in posterior decompression and cement-enhanced pedicle screw fixation. When bone cement leaks through the venous system, it will have serious consequences and even endanger the life of the patient, especially when the bone cement causes intracardiac embolism. Patient concerns: A 70-year-old woman developed chest tightness and decreased blood oxygen saturation following posterior decompression and cement-enhanced pedicle screw fixation. Diagnosis: After the patient was given symptomatic treatment, the symptoms were not relieved, the high-sensitivity troponin I level continued to rise, the electrocardiogram results were abnormal, and chest computed tomography (CT) revealed multiple flaky and strip-shaped dense shadows in the heart. Intervention: The patient underwent removal of foreign bodies from the heart under cardiopulmonary bypass and tricuspid valvuloplasty, removal of intracardiac bone cement, and repair of the tricuspid valve and chordae. Outcome: The patient recovered well postoperatively and was discharged from the hospital after 3 weeks. There were no intracardiac foreign bodies observed on chest CT after the operation. Lessons: For patients with cardiopulmonary discomfort after posterior decompression and bone cement-enhanced pedicle screw fixation, in view of the limitations of radiographic examination, we recommend performing chest CT examination to confirm the diagnosis. For patients with intravascular foreign body embolism, multidisciplinary team joint treatment saves lives.